2001
DOI: 10.1002/1097-0215(20010601)92:5<651::aid-ijc1248>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced apoptosis in human myeloma cell line increases BCL-2/BAX dimer formation and does not result in BAX/BAX homodimerization

Abstract: A popular model of BCL‐2 and BAX involvement in apoptosis suggests that upon apoptosis induction cytosolic BAX translocates to the mitochondria, where it displays the pro‐apoptotic function, which involves its homodimerization. BCL‐2 exerts anti‐apoptotic function by forming heterodimers with BAX, thus neutralizing the pro‐apoptotic activity of the latter. We have shown that irradiation of the human myeloma cell line RPMI‐8226 induced apoptosis as determined by DNA degradation, cytochrome c release into cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Our findings indicate that both proteins were up-regulated after stimulation with high LPS concentrations. This was consistent with a previous report that showed increased expression of Bcl-2 and Bax accompanying increased apoptosis (29). Several studies (29)(30)(31) have demonstrated that pro-and antiapoptotic members of the Bcl-2 family might interact with each other to form homodimers and heterodimers in regulating apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicate that both proteins were up-regulated after stimulation with high LPS concentrations. This was consistent with a previous report that showed increased expression of Bcl-2 and Bax accompanying increased apoptosis (29). Several studies (29)(30)(31) have demonstrated that pro-and antiapoptotic members of the Bcl-2 family might interact with each other to form homodimers and heterodimers in regulating apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of Bax/Bcl-2 ratio is typical for apoptosis. 53 Zong and Thompson have showed that different doses of the same cell death stimulus can trigger different cell death pathways. Thus, lower doses can induce apoptosis, while higher doses can trigger necrosis or other cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…66 Radiation-induced apoptosis is also associated with moderate changes in cytosol-to-mitochondria Bax redistribution. 91 Inhibition of NF-kB activity by the cell-permeable inhibitor SN50 resulted in a decrease in Bcl-2 and A1 and an upregulation of Bax protein levels, shifting the balance toward apoptosis. 46 Furthermore, IL-6-deprivation-induced apoptosis is associated with increased expression of Bax.…”
Section: Proapoptotic Bcl-2 Family Proteins In Myelomamentioning
confidence: 99%
“…In myeloma cells, various apoptotic stimuli 89,91,93 result in the caspase-3-mediated cleavage of Bcl-2 into the 23 kDa proapoptotic Bcl-2 form, which localizes to mitochondria and stimulates the release of cytochrome c into the cytosol. 57 Therefore, cleavage of Bcl-2 in myeloma appears to promote further caspase activation as part of a positive feedback loop.…”
Section: Proapoptotic Bcl-2 Family Proteins In Myelomamentioning
confidence: 99%